The Effect of Mental Health Education on Teenagers’ Capacity for Early Detection of Mental Health - Daulay, Wardiyah; Safira, Annisa (Talenta Publisher, 2024)
Adolescence represents a critical developmental stage during which individuals are highly vulnerable to mental health challenges. Early detection of mental health issues enables adolescents to identify and mitigate potential mental disorders at an initial stage. Mental health education plays a pivotal role in equipping teenagers with the knowledge and skills necessary for early detection. This study aims to evaluate the impact of mental health education on adolescents' knowledge and capacity to engage in early detection of mental health issues, with a focus on students at SMK Swasta Abdi Nusantara. The research adopts a pre-experimental approach using a one-group pretest-posttest design. The study sample comprises 70 respondents, selected through a total sampling technique. Data were analyzed using the Wilcoxon Signed Rank Test, yielding a p-value of 0.000 < 0.05. The findings indicate a significant effect of mental health education on adolescents’ knowledge and ability to conduct early detection of mental health issues. These results underscore the importance of mental health education programs in schools. Community health workers, particularly mental health nurses, are encouraged to optimize mental health initiatives by integrating education programs into school settings, thereby contributing to the prevention of mental disorders among adolescents.